2019
DOI: 10.1002/solr.201900335
|View full text |Cite
|
Sign up to set email alerts
|

Bias‐Dependent Stability of Perovskite Solar Cells Studied Using Natural and Concentrated Sunlight

Abstract: Degradation rates in perovskite solar cells (PSCs) were previously shown to be bias dependent; however, little is known about the mechanisms and driving factors that account for such degradation. Herein, stability studies under concentrated sunlight are demonstrated as a powerful experimental methodology to investigate bias-dependent PSC degradation mechanisms. Stress testing of encapsulated PSCs' stability shows that light intensity is more significant than the illumination dose for PSC degradation under shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…33 Besides, degradation rates in PSCs are also reported to be bias-dependent and different instability mechanisms are found to dominate under different bias conditions. 34 It is reported that the degradation at open-circuit (OC) conditions is light dose-dependent, while at short-circuit (SC), it is observed to be intensity-dependent only. 34,35 Furthermore, reverse bias stability is of paramount importance as the shaded cells in a module can be put to reverse bias by the illuminated cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 Besides, degradation rates in PSCs are also reported to be bias-dependent and different instability mechanisms are found to dominate under different bias conditions. 34 It is reported that the degradation at open-circuit (OC) conditions is light dose-dependent, while at short-circuit (SC), it is observed to be intensity-dependent only. 34,35 Furthermore, reverse bias stability is of paramount importance as the shaded cells in a module can be put to reverse bias by the illuminated cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thin Films Photovoltaics [37], while the concave pattern has been observed in encapsulated cells exposed to different levels of sunlight [9]. In addition, this shape has also been observed in nonencapsulated PSCs under higher relative humidity [11], and in nonencapsulated devices tested under air exposure [38].…”
Section: ) C) Degradation Rate (Dr) Of Three Representative Patterns Of Each Group According To Degradation Levels Suggested By the Probamentioning
confidence: 70%
“…In the case of emerging technologies such as PSCs, no international standards have been fully established and adopted, and most published works have focused on laboratory-scale cells to evaluate the performance, stability and degradation of this technology [8][9][10][11][12][13][14]. Thus, because this technology is in its infancy, insufficient data are available to fully establish or identify the degradation modes and mechanisms of PSCs, the impact on outdoor performance evolution including large devices [15,16].…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…The operational load has significant implications on the degradation mechanisms and measured device lifetime 18 . PSCs' degradation is often (but not always 19 ) fastest at open circuit 18 . Also, in any real application, the solar cell will be operated at MPP.…”
Section: Outdoor Testingmentioning
confidence: 99%